Biosynthesis And Characterization Of Novel Polyhydroxyalkanoate By Cupriavidus Necator PHB-4 Transformant Harboring PHA Synthase Gene Of Chromobacterium SP. USM2 - Ooi , Tin Fong (2011)
The incorporation of a newly identified 3-hydroxy-4-methylvalerate (3H4MV) monomer into the backbone of polyhydroxyalkanoate (PHA) is thought to improve the properties of the resulting polymer. In this study, a transformant of C. necator PHB¯ 4 harboring the PHA synthase gene of Chromobacterium sp. USM2 [C. necator PHB¯4 (phaCCs)] was evaluated for its ability to synthesize novel short-chain and medium-chain-length (SCL-MCL) PHA containing 3H4MV. Fructose or crude palm kernel oil (CPKO) was used as main carbon source together with isocaproic acid (4MV) as precursor to produce the excellent SCL-MCL PHA. 4MV concentration and its feeding time had been identified as important parameters affecting PHA content and monomer composition of the resulting polymer.